Islamic Brand Sahaja in Commercial TV Advertising Messages: Toward the Islamisation of the product - Agus Hermanto; Sa’diyah El Adawiyah; Tria Patrianti (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2022)
Commercial TV advertising can translate everything from the advertiser's goals through communicative, educative, and entertaining messages. As in the commercial TV advertisement message, Sahaja socialises the Islamic brand, which aims to be able to dialogue with the target market of Indonesian Muslims. This study aimed to determine the visual and narrative form of the Islamic brand of Sahaja's commercial TV advertising message. This study uses a qualitative approach with narrative analysis, how do communicators tell stories. The data collection techniques are observing Sahaja's advertising materials and literature study, analysing each ad frame and duration individually, and selecting and grouping according to the research focus for data presentation. In conclusion, Sahaja's commercial TV commercial carries #NawaituSahaja as its creative foundation. It shows a visual story of a happy family living their life and worship with white domination. Five essential keys visible reflections of Islamic brands narrate the form of a brand that identifies with Islamic characteristics. This research is expected to help provide input or reference for further research and considerations in building an Islamic brand.